1998
DOI: 10.1152/jn.1998.80.4.2023
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Activation of Plateaus in Hindlimb Motoneurons of Decerebrate Cats

Abstract: Intracellular recordings were made from hindlimb motoneurons in decerebrate cats to study how synaptic inputs could affect the threshold at which plateau potentials are activated with current injections through the recording microelectrode in the cell body. This study was prompted by recent evidence that the noninactivating inward currents that regeneratively produce the plateau potentials arise (partly) from dendritic conductances, which may be relatively more accessible to synaptic input than to current inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
320
2
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(361 citation statements)
references
References 38 publications
30
320
2
9
Order By: Relevance
“…Heckman and Robert Lee demonstrated that the synaptic current evoked by group Ia afferent stimulation was enhanced by methoxamine application (which can lead to plateau potentials; Lee & Heckman, 1996), David Bennett together with Hultborn and colleagues demonstrated that the threshold current for activating plateau potentials was much lower when the motoneurons were synaptically activated by Ia afferent stimulation. This finding was consistent with activation of these currents near the site of the synaptic input, i.e., on the dendrites (Bennett et al, 1998). Using somatic voltage clamp of mouse motoneurons in spinal cord slice preparations (Carlin et al, 2000a), we demonstrated delayed inward currents in response to step depolarizations and suggested that the delay was caused by the dendritic location of the conductances (Carlin et al, 2000b; see also Booth and Rinzel, 1995;Booth et al, 1997;Muller and Lux, 1993).…”
Section: The Role Of Motoneuron Dendrites In Repetitive Firingsupporting
confidence: 81%
“…Heckman and Robert Lee demonstrated that the synaptic current evoked by group Ia afferent stimulation was enhanced by methoxamine application (which can lead to plateau potentials; Lee & Heckman, 1996), David Bennett together with Hultborn and colleagues demonstrated that the threshold current for activating plateau potentials was much lower when the motoneurons were synaptically activated by Ia afferent stimulation. This finding was consistent with activation of these currents near the site of the synaptic input, i.e., on the dendrites (Bennett et al, 1998). Using somatic voltage clamp of mouse motoneurons in spinal cord slice preparations (Carlin et al, 2000a), we demonstrated delayed inward currents in response to step depolarizations and suggested that the delay was caused by the dendritic location of the conductances (Carlin et al, 2000b; see also Booth and Rinzel, 1995;Booth et al, 1997;Muller and Lux, 1993).…”
Section: The Role Of Motoneuron Dendrites In Repetitive Firingsupporting
confidence: 81%
“…PIC activation may be facilitated by increased excitatory reflexes following spinal cord injury (Baker and Chandler 1987;Li et al 2004b). Synaptic inhibition has been shown to be a key mechanism in the control of motoneuron discharge and dendritic PIC activation (Bennett et al 1998;Hultborn et al 2003), particularly for dendritic sources of inhibition (Bui et al 2008;Venugopal et al 2011). Synaptic inhibition may be altered by changes in inhibitory receptors (Bareyre and Schwab 2003;Khristy et al 2009) and alterations in the strength of segmental inhibitory synaptic inputs (Shapiro 1997;Norton et al 2008).…”
Section: Mechanisms Underlying Pic Dysregulation After Scimentioning
confidence: 99%
“…The activation of dendritic persistent inward currents in motoneurons can lead to the production of electrical events known as plateau potentials (Schwindt and Crill, 1980;Hounsgaard and Kiehn, 1993;Lee and Heckman, 1996;Bennett et al, 1998). We first investigated whether calcium-dependent plateau potentials could be produced by mouse motoneurons.…”
Section: Plateau Potentialsmentioning
confidence: 99%
“…However, voltage-activated calcium currents in motoneuron dendrites, which generate "persistent inward currents" (PICs), appear to ensure integration of even distal inputs Li and Bennett, 2003). PICs generate plateau potentials (Hounsgaard and Kiehn, 1989;Lee and Heckman, 1996) and amplify synaptic inputs to motoneurons, both excitatory (Brownstone et al, 1994;Bennett et al, 1998;Lee and Heckman, 2000;Jones and Lee, 2006;Powers et al, 2008) and inhibitory (Hultborn et al, 2003;Kuo et al, 2003;Bui et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%